PRAKTIK KUASA DI BALIK WACANA TAMBANG PASIR BESI (Studi CDA Terhadap Pemberitaan Surat Kabar Flores Pos dan Expo NTT Selama Masa Kampanye) - NGGA’A, PAULUS KRIST (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2016)
This study intends to reveal the practice of power that works behind the iron sand mining discourse produced by the local media (Flores Post and Expo NTT) against two candidates regent/vice regent, partner Don Bosco M. Wangge/ Dominikus M. Mere (Darmawan package) and couples Marselinus Y.W Petu/Djafar Achmad (package MD) that took place during the election campaign round Ende period 2014-2019. Local political dynamics concretely evident in the election process. As one form of political constestation, there are a variety of issues with a variety of interests and strategies that are played for the sake of gain votes (voter) and won the election process. Including, through the use of language that reflects the ongoing exercise of power. The use of language in relations of power can be seen clearly through the fight discourse that occurs through the mass media. Strengthening discourse iron sand mining in the news flores post and expo ntt during the campaign, in fact an expression of conflict of interest between the parties involved with various backgrounds. Existing conditions illustrates that the practice of discourse in the mass media is not something neutral. Behind the news , there is a pattern of power relations influence, direct and try to shape the reality of the reader's mind. To dismantle what is behind the text, the authors use model Norman Fairclough CDA strategy as a research framework with fixed understand the concept of discourse in the light of Foucault's thought. The findings indicate that the iron sand mining discourse production is dominated by groups represented in patriarchal authority (local elites), the power authority of the clergy/church (shepherd to his sheep) and the power of social institutions (mosalaki to ana kalo fai walo) which interest saved dominance they receive to perpetuate their power in society structure Ende. This illustrates the potential of that discourse can be produced by anyone in order to run power to influence others. As a reader, it takes a critical awareness to understand the social reality that infiltrated in these texts. Keywords: Power, Discourse, Mass Media, Election.